Animal Communication Techniques of Study and Results of Research - Sebeok, Thomas A. (Indiana University Press, 1968)
Twenty-four original articles by world-renowned experts in the fields of zoology and psychology present an extensive survey of the "state of the art" as of the late 1960's. Topics range from a review of the techniques of study of animal communication and the mechanics of communication to communication the practical uses and implications of these studies for related fields of study. Contributors are Richard D. Alexander, Stuart A. Altmann, Gregory Bateson; W. Frank Blair, Rene-Guy Busnel, A. Richard Diebold, Hubert Frings, Mable Frings, Donald R. Griffin, Jeremy J. Hatch, Charles F. Hockett, Barbara I. Hooker, Peter H. Klopfer, Eric H. Lenneberg, Peter Marler, Abraham A. Moles, Thomas C. Poulter, J. P. Scott, Thomas A. Sebeok, W. John Smith, William N. Tavolga, Gunter Tembrock, Adrian M. Wenner, and Edward 0. Wilson.